The effect of shadow economy, life expectancy, education, and income on CO2 emissions: an analysis of BRICS countries - Sart, Gamze; Bayar, Yılmaz; Sezgin, Funda H.; Danilina, Marina; Karagöz, Eray (Frontiers in Environmental Science, 2025)
Environmental impairment has become one of the leading global concerns since the 1950s, and the drivers of increasing global CO2 emissions have begun to be explored extensively. This study investigates the short and long term effects of the shadow economy, life expectancy, education, and income on CO2 emissions in the BRICS countries during the 1993–2020 period, accounting for cross-sectional dependence and heterogeneity using second-generation cointegration tests, the augmented mean group (AMG) estimator, and causality tests. The results of the causality test reveal a unidirectional causality from the shadow economy, education, and income to CO2 emissions and a bidirectional causal nexus between life expectancy and CO2 emissions. The results of the AMG estimation show that the shadow economy, life expectancy, and income positively affect CO2 emissions in BRICS countries, while improvements in education negatively impact CO2 emissions. Therefore, institutional and legal arrangements to combat the shadow economy would be beneficial in decreasing CO2 emissions.